SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB PADA BALAI PENGKAJIAN TEKNOLOGI PERTANIAN JAWA TIMUR - Alfian, Aris; Andoko, Banni Satria; Sophia, Evy (DINAMIKA DOTCOM, 2014)
Library Information Systems is a computer application that serves to process data library books. Includes data collection members, registration books, number books, authors, publishers, book classification, and shelves. The purpose of this research is the realization of an information system that is able to help officers determine a collection of books, the status of the book, any book ever borrowed by members, and to know that there are graphs borrowing at library Balai Pengkajian Teknologi Pertanian Jawa Timur (BPTP Jatim) in the not old.The data used for the realization of this system get through direct interviews to officers BPTP Jatim libraries. For the method of analysis and design of information systems using the ERD and UML data model as a process model. As well as using the PHP programming language and MySQL database in the making of the program.Once the system is implemented in BPTP Jatim, officials initially had difficulty in knowing a collection of books, the status of the book, any book ever borrowed members, and helped monitor the loan now. Officers no longer need to open the old files to find out what books ever borrowed members. Officers could find out through this information system. Besides lending officers can also monitor the status of the book, members who frequent borrowing, any book that is often borrowed by the chart provided. Keywords: Library Information Systems, BPTP Jatim, UML, PHP, MySQL